Development of technological capabilities: problems in developing countries and suggestions for Vietnam - Ha, Mai; Hai, Nguyen Hoang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
Development of technological capabilities is crucial part of strategies for nations. It is backgrounds to get higher labor productivity and quality of products, and to offer competitive advantages in international markets. Studies and assessments conducted abroad also show well that tasks to build up and to develop technological capabilities in developing countries face more tough difficulties than developed countries do because they remain still limited in resources and institutional aspects particularly. In order to go over barriers and disadvantages for development of technological capabilities, developing countries should set up and implement reasonable and wise strategies and policies to secure enough resources and policy-based tools to offer in-time supports in process of learning and accumulating knowledge and experiences for development of technological capabilities in every sectors. This paper would put first accents to clarify certain aspects related to technological capabilities such as: What are technological capabilities? How to get them? Which problems do developing countries should pay attentions to in their efforts for development of technological capabilities, differently from developed nations? Where are the top key aspects of attentions of Vietnam in its efforts for development of technological capabilities in close future? Code: 16080501